Added Soy Proteins in Processed Meats in Malaysia - Babji, Abdul Salam; Abdul Wahab, Adnan; Abdullah, Aminah (1984)
Two methods were used to determine the amount of soya protein added in some local processed meat products. The use of soya protein in processed meat formulation is increasing because of the high cost of meat. At present there are no strict measures to ensure the proper use of food extenders in meat and other products. Results from this study indicate that most meat products such as burgers and frankfurters produced locally contain between 5 - 25% added soya protein. The enzymatic method of determining soya protein was found to be more sensitive than the centrifugation method. However, for routine quality control work, the AOAC (1980) centrifugation method would be more practical and economical.